2006
DOI: 10.1038/sj.eye.6702542
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prostaglandin analogues on the blood aqueous barrier and corneal thickness of phakic patients with primary open-angle glaucoma and ocular hypertension

Abstract: Purpose: To evaluate the effects of topical latanoprost, travoprost, and bimatoprost on the blood-aqueous barrier and central corneal thickness (CCT) of patients with primary open-angle glaucoma (POAG) and ocular hypertension (OHT). Design: Prospective, randomized, maskedobserver, crossover clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
3
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 30 publications
(42 reference statements)
1
37
3
2
Order By: Relevance
“…Most of the recent studies have showed that prostaglandin analogues could decrease the central corneal thickness (CCT) values [13][14][15][16][17][18][19]. Lee and Cho [13] observed that latanoprost significantly reduced CCT in normal-tension glaucoma patients after 5 years of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the recent studies have showed that prostaglandin analogues could decrease the central corneal thickness (CCT) values [13][14][15][16][17][18][19]. Lee and Cho [13] observed that latanoprost significantly reduced CCT in normal-tension glaucoma patients after 5 years of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Sen, et al [15] observed a significant reduction in CCT at the 6 th , 12 th , and 24 th months in 188 eyes of 94 patients under topical latanoprost and bimatoprost medications. Arcieri, et al [16] found a statistically significant CCT reduction (0.6%) in 34 glaucoma patients within the first month of bimatoprost treatment, but no change was observed in latanoprost and travoprost treatment groups. In 69 eyes, Zhong, et al [17] determined that topical therapy with PGs is associated with CCT reduction and latanoprost, travoprost, and bimatoprost have a similar effect on CCT.…”
Section: Resultsmentioning
confidence: 99%
“…more effective, reliable, probable, etc) than q, e.g., IOP reduction obtained with travoprost was significantly higher than that obtained with latanoprost [1]; p > q means that p is more preferred (but not significantly) than q, e.g., travoprost is more effective than timolol in lowering IOP in patients with open-angle glaucoma or ocular hypertension [14]; and p q means p is more or less equivalently preferred to q, e.g., travoprost appears to be equivalent to bimatoprost and latanoprost [14]. It should be noted that p q does not simply lead to p > q since p > q implies that preference of p to q is not significant.…”
Section: Notations and Definitionsmentioning
confidence: 99%
“…The comparisons of drugs on IOP reduction are often expressed in the form of e.g. travoprost was superior to latanoprost [6] or travoprost appears to be equivalent to bimatoprost and latanoprost [14] or IOP reduction obtained with travoprost was significantly higher than that obtained with latanoprost [1] (note travoprost, bimatoprost, latanopros, and timolol are all names of drugs for IOP reduction).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation